Impact of Strategic Entrepreneurial on Strategic Decision-Making: A Field Study in North Oil Company/Kirkuk - Mobard Sarhid, Ahmed; Abdulraheem Said Alubadi , Sanaa (Journal of Economics and Administrative Sciences, 2024)
The scope of the concept of strategic entrepreneurship has expanded within organizations, and interpretations of this concept have multiplied. It is a critical element that must be considered across the various related dimensions, because it is of great importance as it has the ability to change the direction of business organizations today in addition to the support it provides for strategic decisions, resources and industrial education. The research initially identified the theoretical gap between the existing intellectual proposals put forward by the researchers, which paved the way for practical application within the North Oil Company / Kirkuk. The main tool used in collecting data and information was the questionnaire, which was presented to a group of arbitrators to be modified and appropriate to the field and the ease of answering it by the researched sample. The questionnaire was distributed to middle management within the company at the rank of department manager and Division manager. A total of 56 questionnaires were distributed, of which 53 were retrieved. The Amos program was used in addition to the statistical program Excel and SBSS, and the research aims to identify the basic dimensions of entrepreneurship and strategic decisions. The study used the descriptive analytical method. Moreover, one of the most prominent results of the research is that strategic entrepreneurship is the main factor for organizations that wish to obtain excellence and prosperity and have the ability to continue in a competitive environment, where strategic entrepreneurship avoids weaknesses and exploitation. strengths. For the organization, this of course requires decisive and quick strategic decisions